2019
DOI: 10.1155/2019/3715481
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antifungal and Antivirulence Activities of Biologically Synthesized Ethanolic Extract of Propolis-Loaded PLGA Nanoparticles against Candida albicans

Abstract: Propolis is a natural substance and consists of bioactive compounds, which gives it antioxidant and antimicrobial properties. However, the use of propolis is limited by the low solubility in aqueous solutions. Thus, nanoparticles may be likely to accomplish enhanced delivery of poorly water-soluble phytomedicine. The aim of the present study was to fabricate and evaluate the biological activity of ethanolic extract of propolis-loaded poly(lactic-co-glycolic acid) nanoparticles (EEP-NPs). The EEP-NPs were prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 70 publications
2
33
0
1
Order By: Relevance
“…The results of this study point to the antimicrobial activity of ethanolic extract of Iranian Propolis that is provided from Qazvin province. Studies have shown that Propolis has a significant antibacterial, antiprotozoon, anti-viral and antifungal effects [15,16,17,18]. Although, some reports have identified, despite having a great inhibitory influence on the growth of Gram-positive bacteria, it has little effect on Gram-negative bacteria [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study point to the antimicrobial activity of ethanolic extract of Iranian Propolis that is provided from Qazvin province. Studies have shown that Propolis has a significant antibacterial, antiprotozoon, anti-viral and antifungal effects [15,16,17,18]. Although, some reports have identified, despite having a great inhibitory influence on the growth of Gram-positive bacteria, it has little effect on Gram-negative bacteria [17].…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, the propolis extract serially diluted twofold in a 96-well microplate. First, 100 L double serial dilution (1,2,8,16,32,64,128,256, 512 mg/ml) of Propolis extract was prepared in Muller Hinton broth tubes. Then to each tube 5 × 10 5 CFU / ml per milliliters of broth from microbial suspension of Staphylococcus aureus: S.aureus and Pseudomonas aeruginosa: P. aeruginosa equals 0.5 McFarland was added.…”
Section: Antibacterial Assaysmentioning
confidence: 99%
“…The elution was carried out with a linear gradient and a flow rate of 1.0 mL/min. The detection was monitored at 267 nm and the components were identified in comparison with commercial standards (Gallic acid, Quercetin, Pinocembrin, Chrysin, and Galangin) [ 15 ]. All standards were purchased from Sigma-Aldrich, St. Louis, MO, USA.…”
Section: Methodsmentioning
confidence: 99%
“…Inhibited the virulence factors of C. albicans, such as adhesion, hyphal germination, biofilm formation, and invasion (1 and 2 mg/mL) [88] MFC: medium fungicidal concentration.…”
Section: Candidiasismentioning
confidence: 99%